Design and fabrication of permanent magnet configuration to concentrate magnetic field strength - Chew, Yong Chan (2019)
Permanent magnets are often preferred over electromagnets for smaller applications, as the latter are usually prodigious in size, and are perpetually tethered to a power supply. In addition to these reasons, the growth in demand for stronger magnetic fields in devices that are becoming increasingly smaller drives the need to investigate the optimal utilization and confinement of the generated magnetic flux of permanent magnets to achieve a stronger magnetic field. The aim of this report is to investigate the use of Halbach cylinders, which is the cylindrical arrangement of permanent magnets in configurations such that the magnetic field is concentrated in the inner diameter of the cylinder, with the eventual fabrication of a magnet configuration to concentrate magnetic field strength within a cuboidal region of interest with 10 mm dimensions. The report first compared six approximated Halbach configurations that employ only commercially available magnet sizes and determined the configuration that resulted in the strongest magnetic field, using two-dimensional simulations conducted on finite element analysis software, FEMM 4.2. Subsequent simulations include studying the effects of increasing the dimensions of the magnet segments, and the effects of nested cylinders and the findings showed that the latter is the more material-efficient method of increasing magnetic field strength. Next, the report compared the two-dimensional simulation results with that of an actual 3D model that was fabricated, and the results concluded that the fabricated model yielded a significantly lower magnetic field strength. Sources of the loss in field strength were also discussed in the report. Then, the report examined how the amount of losses changed across three different layered configurations and concluded that a configuration with fewer layers experienced lower losses. Lastly, the report provided several future recommendations, which include the use of magnetic materials with high values of permeability as shielding materials to better direct the magnetic flux, and to achieve an optimal trade-off between the magnetic field strength and homogeneity of the generated field.